Aβ misfolding in blood plasma is inversely associated with body mass index even in middle adulthood - Möllers, Tobias; Stocker, Hannah; Perna, Laura; Nabers, Andreas; Rujescu, Dan; Hartmann, Annette M.; Holleczek, Bernd; Schöttker, Ben; Gerwert, Klaus; Brenner, Hermann (Alzheimer's research & therapy, 2021)
To understand the potential for early intervention and prevention measures in Alzheimer’s disease, the association between risk factors and early pathological change needs to be assessed. Hence, the aim of this study was to determine whether risk factors of Alzheimer’s clinical syndrome (clinical AD), such as body mass index (BMI), are associated with Aβ misfolding in blood, a strong risk marker for AD among older adults.
Gesehen am 08.11.2021